Hyperphosphatemia induces senescence in human endothelial cells by increasing endothelin‐1 production. Issue 6 (31st August 2017) - Olmos, Gemma; Martínez‐Miguel, Patricia; Alcalde‐Estevez, Elena; Medrano, Diana; Sosa, Patricia; Rodríguez‐Mañas, Leocadio; Naves‐Diaz, Manuel; Rodríguez‐Puyol, Diego; Ruiz‐Torres, María Piedad; López‐Ongil, Susana
Summary: Hyperphosphatemia is related to some pathologies, affecting vascular cell behavior. This work analyzes whether high concentration of extracellular phosphate induces endothelial senescence through up‐regulation of endothelin‐1 (ET‐1), exploring the mechanisms involved. The phosphate donor β‐glycerophosphate (BGP) in human endothelial cells increased ET‐1 production, endothelin‐converting enzyme‐1 (ECE‐1) protein, and mRNA expression, which depend on the AP‐1 activation through ROS production. In parallel, BGP also induced endothelial senescence by increasing p16 expression and the senescence‐associated β‐galactosidase (SA‐ß‐GAL) activity. ET‐1 itself was able to induce endothelial senescence, increasing p16 expression and SA‐ß‐GAL activity. In addition, senescence induced by BGP was blocked when different ET‐1 system antagonists were used. BGP increased ROS production at short times, and the presence of antioxidants prevented the effect of BGP on AP1 activation, ECE‐1 expression, and endothelial senescence. These findings were confirmed in vivo with two animal models in which phosphate serum levels were increased: seven/eight nephrectomized rats as chronic kidney disease models fed on a high phosphate diet and aged mice. Both models showed hyperphosphatemia, higher levels of ET‐1, and up‐regulation in aortic ECE‐1, suggesting a direct relationship between hyperphosphatemia and ET‐1. Present results point to a new and relevant role of hyperphosphatemia on the regulation of ET‐1 system and senescence induction at endothelial level, both in endothelial cells and aorta from two animal models. The mechanism involved showed a higher ROS production, which probably activates AP‐1 transcription factor and, as a result, ECE‐1 expression, increasing ET‐1 synthesis, which in consequence induces endothelial senescence.